Structure-function relationships of haloalkane dehalogenase enzymes - Chaloupková, Radka, 1978-; Koča, Jaroslav, 1955-2021; Masarykova univerzita. Národní centrum pro výzkum biomolekul (2008)
Disertační práce popisuje strukturu a funkci dvou halogenalkandehalogenas: LinB z Sphingobium japonicum UT26 a DbjA z Bradyrhizobium japonicum USDA110. Práce zahrnuje expresi a purifikaci divokých typů a mutantních enzymů, jejich strukturní charakterizaci metodou cirkulárního dichroismu, měření enzymové aktivity, stanovení kinetických konstant ve stacionárním a tranzitním stavu a termodynamickou analýzu jejich enantioselektivity. Práce shrnuta v kapitole 1 je soustředěna na detailní pochopení katalytického mechanismu halogenalkandehalogenasy LinB. Kinetika ve stacionárním a tranzitním stavu byla měřena se substráty 1-chlorhexanem, chlorcyklohexanem and bromcyklohexanem.
This thesis describes the structure and function of two haloalkane dehalogenases LinB from Sphingobium japonicum UT26 and DbjA from Bradyrhizobium japonicum USDA110. The work covers mutagenesis, expression and purification of the wild type and mutant enzymes, their structural characterisation by using the method of circular dichroism spectroscopy, measurement of activity, determination of steady-state and presteady-state kinetic constants and thermodynamic analysis of their enantioselectivity. The work reported in Chapter 1 is aimed at detailed insight into the kinetic mechanism of the haloalkane dehalogenase LinB. The steady-state and presteady-state kinetics of the enzyme were measured with 1-chlorohexane, chlorocyclohexane, and bromocyclohexane as model substrates.
Vedoucí práce: Jaroslav Koča.
Dizertace (Ph.D.)--Masarykova univerzita, Přírodovědecká fakulta, 2008.
Keywords: enzymatická aktivita; enantioselektivita enzymu; halogenalkandehalogenasa; spektroskopie cirkulárního dichroismu; stabilita enzymu; substrátová specifita; circular dichrosim spectroscopy; enzymatic activity; enzyme enantioselectivity; enzyme stability; haloalkane dehalogenase; substrate specificity; disertace; dissertations